Understanding the role of entrepreneurial orientation in Junior Enterprises - Almeida, João (2019)
The promotion of entrepreneurial behaviour and competences among students is being highlighted by researchers and policy-makers, as a mean to promote social and economic development. Therefore, the search for the most effective teaching methods, programs and curricula, as well as extra-curricular activities, is a concern of many teachers and educators. This study focus on Junior Enterprises (JEs), a non-profit organization, constituted by university students with the purpose of providing the context that mimics an actual business environment, in order to enhance the entrepreneurial competences of their members. Currently, the JE network is present in more than 500 universities worldwide, accounting for more than 990 JEs and 50000 students. Although its relevance, JEs are an ill-studied subject, with only a limited number of empirical studies focused on this type of organization. This study aims at fulfilling this gap by providing evidence that JEs are an adequate test-bed for students to learn and practice entrepreneurship. Based on these assumptions, this study explores the strategic orientations and its impact on JEs performance, in order to assess if JE behaves similarly to an actual company. Thus, an Entrepreneurial Orientation (EO) measurement instrument adapted to JEs is developed and then used to test the effect of EO dimensions on the performance of JEs. The regression analysis conducted with the new dimensions showed that EO positively influences the performance of JEs, having an important role in the development of the JE and consequently in the development of the students.